Educators engaged in meaning-making about their work : using an expanding circles model of governance, grounded in sociocratic principles, to improve the work educators do - Joyce, Pauline Therese (Curtin University, 2011)
The early part of the 21st century saw a dramatic shift in Western cultures away from representative democracy to a more participatory or deep democracy. Advocates of this new democracy consider that finding solutions to the problems that confront our world, on a global scale, are too complex to be left in the hands of elected officials. As a result, public participation, or community engagement, has become a way for organisations to dig deeper in order to find more resilient and sustainable solutions to difficult problems. This form of democracy presupposes informed citizens who are communicatively competent to take their place as fully participating members of a democratic society. As schools are considered by some experts to be the best place to develop the skills required for democratic participation it made me question the reality of making such a claim. Overwhelmingly, schools continue to function under endowed, autocratic leadership where there is little opportunity for democratic participation.In undertaking my research I took on the role of co-participant in two primary schools to explore the question: What happens when teachers are given greater opportunities to deliberate and make decisions about the work they do? How and why it happened became the focus of an auto-ethnographic study with co-participants from the two schools over a period of two and a half years (2008-2010). As the researcher, I coached, mentored and guided individual teachers, principals, teams of teachers and leadership teams through a restructuring and reculturing process that began with the introduction of a new governance model, sociocracy, where decisions are made by the socios, people in close social proximity to one another, rather than the demos, the general populace. The complex and emerging nature of this research determined that I use a multi paradigmatic design, as espoused by Guba (1990), in order to respond to the turbulent nature of the research field. My design allowed me to continually shift focus to reveal multiple perspectives, my own and “Other”, as I mined the rich underlay of data that emerged out of my interactions in each school. The quality standards used to measure the worth of this project are aligned to the methodologies chosen; they shift throughout the project as I consciously choose the best way to reveal the knowledge gained from my interactions in the field. I have interwoven theory, practice and multiple voices throughout the text as a way of balancing the reported disconnect that teachers feel between policy and practice.The outcome of this research is a holistic, scalable organisational framework for schools to use as a way of creating resilient learning organisations that adapt and improve in a constant state of be(com)ing.